Failure mechanisms of coral aggregate concrete under compression-shear loading: Experimental investigation and mesoscale simulation - Dongpeng Ma; Xiaona Huang; Zhongyu Lu (Case Studies in Construction Materials)
Coral aggregate concrete (CAC) is a vital material for island and reef construction, where structures are frequently subjected to compressive-shear loading. Understanding the failure mechanisms of CAC under such conditions is of urgent importance. This study systematically investigated the effects of different indenter angles on the mechanical properties and failure mechanisms of CAC through combined experimental and mesoscale simulation approaches. The experimental results demonstrate that under a constant loading rate of 1 mm/min, the peak normal stress remained relatively stable (44.3–47.0 MPa) within the 0°-15° range. However, when the angle increased to 25°, the peak stress dropped sharply by 28.8 % (to 31.9 MPa), accompanied by a transition from compressive failure to shear failure along with the formation of shear bands and aggregate fracture. The nonlinear variation was accurately characterized by the stress invariant failure criterion, yielding a correlation coefficient of 0.997. Furthermore, the efficiencies of both collision detection algorithms, which are essential for generating mesoscale models, are compared. Mesoscale simulations reveal that at 5° indenter angle, damage initiated as compressive failure in the interfacial transition zone (ITZ), whereas at 25°, shear strain led to ITZ element failure, resulting in oblique crack propagation through aggregates and consequent abrupt loss of load-bearing capacity. The close agreement between simulation results and experimental data validated the reliability of the model.